2017
DOI: 10.1038/s41598-017-12552-8
|View full text |Cite
|
Sign up to set email alerts
|

Cortical afferents onto the nucleus Reticularis thalami promote plasticity of low-threshold excitability through GluN2C-NMDARs

Abstract: Thalamus and cortex represent a highly integrated processing unit that elaborates sensory representations. Interposed between cortex and thalamus, the nucleus Reticularis thalami (nRt) receives strong cortical glutamatergic input and mediates top-down inhibitory feedback to thalamus. Despite growing appreciation that the nRt is integral for thalamocortical functions from sleep to attentional wakefulness, we still face considerable gaps in the synaptic bases for cortico-nRt communication and plastic regulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…2E1, E2). NMDA/AMPA ratios were comparable to previous studies in 148 sensory TRN and thalamus (Fernandez et al, 2017). Moreover, the TRN-EPSCs had a twice-149…”
Section: And the Retrosplenial Cortexsupporting
confidence: 82%
“…2E1, E2). NMDA/AMPA ratios were comparable to previous studies in 148 sensory TRN and thalamus (Fernandez et al, 2017). Moreover, the TRN-EPSCs had a twice-149…”
Section: And the Retrosplenial Cortexsupporting
confidence: 82%
“…This finding is also supported by minimal stimulation studies that suggest the presence of NMDA receptors with lower Mg 21 sensitivity at both of these synaptic inputs onto nRT neurons (Deleuze and Huguenard, 2016). Recently it has been identified that the GluN2C-containing receptors at the cortico-nRT synapses may induce a form of plasticity that involves Ca 21 entry and facilitation of low-threshold Ca 21 channels, potentially T-type channels (Fernandez et al, 2017). However, because of the use of pharmacological agents that modulate both GluN2C-and GluN2Dcontaining receptors and lack of use of knockout approach, it is possible that some of these effects are mediated by GluN2D-containing receptors, which are also enriched in nRT neurons (Yamasaki et al, 2014;Alsaad et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…The neurons in nRT receive glutamatergic collaterals from cortical pyramidal neurons and thalamic relay neurons. Using pharmacological tools, it has been suggested that both thalamo-nRT and cortico-nRT synapses express GluN2C-containing NMDA receptors (Astori and Luthi, 2013;Fernandez et al, 2017). This finding is also supported by minimal stimulation studies that suggest the presence of NMDA receptors with lower Mg 21 sensitivity at both of these synaptic inputs onto nRT neurons (Deleuze and Huguenard, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, one important property of GluN2C receptors is the lower sensitivity to Mg 2+ block compared to GluN2A and GluN2B receptors (Burnashev et al, ; Kuner & Schoepfer, ; Monyer, Burnashev, Laurie, Sakmann, & Seeburg, ; Monyer et al, ). This property allows GluN2C receptors to be activated by ambient glutamate at resting membrane potential and contributes to higher NMDAR activity at resting potential in some brain regions, such as in layer 4 of barrel cortex (Binshtok, Fleidervish, Sprengel, & Gutnick, ) and reticular thalamic nuclei (Fernandez et al, ; Zhang, Llinas, & Lisman, ).…”
Section: Functional Properties Of Glun2cmentioning
confidence: 99%